Effect of fermented garlic extract containing nitric oxide on radial artery pulse waves in hypertension patients: a feasibility observational study - Kim, Jihye; Kim, Gyeong cheul; Kang, HeeJung; Jeon, Youngju (Frontiers in Nutrition, 2025)
BackgroundThis study aimed to evaluate the effect of fermented garlic extract (FGE) containing nitric oxide (NO) on arterial pulse waves in hypertension patients using a noninvasive radial artery tonometry device.Materials and methodsForty-one participants were recruited for this study investigating changes in arterial pulse wave characteristics following the ingestion of FGE containing NO over a 2-week period. Arterial pulse wave measurements were taken before and 15, 20, and 25 min after FGE administration and 2 weeks after the end of the ingestion period.ResultsOne participant withdrew, and five participants refused to undergo pulse wave measurements. These six participants were excluded, resulting in 35 participants being included for analysis. Fifteen minutes after the administration of FGE with NO, the systolic and diastolic blood pressure (BP) significantly decreased. The radial augmentation index (RAI), width (w), width/time (w/t) ratio, and stroke volume index (SVI) significantly decreased, while the mean pulse width significantly increased. Notably, the RAI, w, w/t ratio, and SVI exhibited a decreasing trend at 15, 20, and 25 min compared to the values before the administration of FGE. After 2 weeks of ingestion, no pulse wave variables showed significant changes compared to those before the administration of FGE.ConclusionThe oral administration of low-dose FGE containing NO showed acute positive effects on the wrist artery, including a reduction in BP and an improvement in arterial stiffness. These findings suggest that this study successfully evaluated the effects of FGE containing NO using quantitative and objective pulse parameters as noninvasive indicators.